2020
DOI: 10.1007/s11947-020-02465-2
|View full text |Cite
|
Sign up to set email alerts
|

Active Whey Protein Edible Films and Coatings Incorporating Lactobacillus buchneri for Penicillium nordicum Control in Cheese

Abstract: Fungal contamination of food is responsible for health issues and food waste. In this work, the incorporation of a lactic acid bacteria (LAB) with antifungal properties (Lactobacillus buchneri UTAD104) into whey protein-based films and coatings was tested for the control of an ochratoxigenic fungi (Penicillium nordicum) in a cheese matrix. The incorporation of L. buchneri cells resulted in thicker films with less luminosity than control films and colour alteration. Nevertheless, cells inclusion did not alter m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 68 publications
(103 reference statements)
4
17
1
1
Order By: Relevance
“…It also suppressed lipolytic bacteria growth on day 1; these microorganisms were no longer detectable (<1 log 10 CFU/g) in CC + C + Lh samples during the rest of the storage period compared with control and plain coated cheeses samples (1.5–1 log 10 CFU/g; Figure 3 d). This is in agreement with Guimarães et al (2020) [ 51 ], where whey protein coatings containing L. buchneri cells prevented microbial spoilage in cheese for at least 30 days.…”
Section: Resultssupporting
confidence: 92%
“…It also suppressed lipolytic bacteria growth on day 1; these microorganisms were no longer detectable (<1 log 10 CFU/g) in CC + C + Lh samples during the rest of the storage period compared with control and plain coated cheeses samples (1.5–1 log 10 CFU/g; Figure 3 d). This is in agreement with Guimarães et al (2020) [ 51 ], where whey protein coatings containing L. buchneri cells prevented microbial spoilage in cheese for at least 30 days.…”
Section: Resultssupporting
confidence: 92%
“…These peptides may lead to damage of fungal cell membranes and alter their permeability (Al-Majali et al, 2007). However, the inability of P-T hydrolysate for the complete inhibition of fungi in soft cheese may be due to slower transmission of antimicrobial agents in food system (Cagri et al, 2002).These results agreed with Guimarães et al (2020) who revealed the delayed development of Penicillium nordicum on cheese surface coated with WPC-edible film. These findings are similar to those stated by Shashikumar and Puranik (2012) who used lactoferrin as one of potent antifungal whey protein increased shelf life of paneer cheese.This results agreed with Vogel et al(2002) who reported that potent antimicrobial effect of lactofericcin peptide may be attributed to their richness with tryptophan and Arginine amino acids in their sequences.Other studies carried out by Medeiros et al (2014) revealed the complete absence of fungal proliferation up to 20 days in cheese coated lysozyme solution.…”
Section: Discussionsupporting
confidence: 83%
“…4b). The antifungal action of lactic acid bacteria, including L. plantarum , Levilactobacillus brevis , Limosilactobacillus reuteri , Limosilactobacillus fermentum and L. buchneri strains, has been documented previously and corresponded to the production of acetic, lactic and phenyllactic acids (Gerez et al ., 2009; Barman et al ., 2017; Guimarães et al ., 2020; Abouloifa et al ., 2021). These organic compounds have been explained as having potential antifungal biopreservative activity in another investigation against Aspergillus fumigatus and Rhizopus stolonifer (Prema et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…As well as being carriers for bioactive compounds such as vitamins, enzymes and antioxidants, edible films have recently been developed to immobilise probiotics, because of their sustainable nature and various applications in foods (Falguera et al, 2011). Earlier investigations have studied the influence of biomatrix types, probiotic species and prebiotics on the development of probiotic-containing edible films (Ebrahimi et al, 2018;Guimarães et al, 2020;Davachi et al, 2021). Mozaffarzogh et al (2020) developed and applied the carboxymethyl cellulose (CMC)-sodium caseinate film containing probiotic to maintain the quality of fresh trout fillets.…”
Section: Introductionmentioning
confidence: 99%